Natural leisure spaces in long-term care homes: challenging assumptions about successful aging through meaningful living. Issue 1 (1st January 2017) - Whyte, Colleen; Fortune, Darla
ABSTRACT: In promoting high physical activity and productive engagement as the motto of successful aging, society has cast individuals living in long-term care (LTC) homes as aging unsuccessfully [Holstein, M. B., and M. Minkler. 2003. "Self, Society and the 'New Gerontology'." The Gerontologist 43: 787–796]. The purpose of this paper is to explore ways natural leisure spaces within an LTC home can challenge deficit-based assumptions of decline and dependence in later life. Interviews were conducted with 9 residents, 8 family members and 11 staff recruited from one mid-sized LTC home in Ontario, Canada. The study used a hermeneutic phenomenological method, as described by van Manen [1997. Researching Lived Experience: Human Science for an Action Sensitive Pedagogy . London, ON: The Althouse Press]. Lived experiences of participants throughout the interviews revealed how natural leisure spaces sparked continued expressions of individuality, opportunities to nurture relationships and maintain family social roles.